Biophysics of DNA-protein interactions from single molecules to biological systems - Williams, Mark C. (Mark Christian).; Maher, L. James (Louis James) 1960-.; SpringerLink (Online service). (New York Springer, 2011)
This book presents a concise overview of current research on the biophysics of DNA-protein interactions. A wide range of new and classical methods are presented by authors investigating physical mechanisms by which proteins interact with DNA. For example, several chapters address the mechanisms by which proteins search for and recognize specific binding sites on DNA, a process critical for cellular function. Single molecule methods such as force spectroscopy as well as fluorescence imaging and tracking are described in these chapters as well as other parts of the book that address the dynamics of protein-DNA interactions. Other important topics include the mechanisms by which proteins engage DNA sequences and/or alter DNA structure. These simple but important model interactions are then placed in the broader biological context with discussion of larger protein-DNA complexes . Topics include replication forks, recombination complexes, DNA repair interactions, and ultimately, methods to understand the chromatin context of the cell nucleus. This book will be of interest to readers who wish to explore current biophysical approaches to DNA-protein interactions across multiple levels of biological complexity.
Introduction -- Nonspecific DNA Binding: Searching DNA and Altering DNA Properties -- DNA Search Theory -- DNA Search, Hopping vs. Sliding -- SSB DNA Search -- HN-S Proteins or DNA Sliding Search -- Processivity Clamp -- DNA Bending Proteins -- Kinetics of DNA Binding and Bending by Proteins -- Modes of DNA Interaction by Architectural Proteins -- Complex Protein-DNA Interactions -- DNA Looping by Repressor Proteins -- NF-kappaB Transcription Factor Crystallography -- Replication Complex -- DNA Recombination Complexes -- DNA Binding by Alkyltransferase Repair Proteins -- DNA Polymerase Crystallography -- Polymerase Switching in Response to DNA Damage -- Single Molecule Studies on Chromatin -- Regulation of Chromosome Conformation in Cells -- Nucleosome Positioning Across Genomes.
Electronic reproduction.
Keywords: DNA-protein interactions; Molecular biology; Electronic books